Coordination Polymers Based on Amphiphilic Oligomeric Silsesquioxanes and Transition Metal Ions (Co2 +, Ni2+): Structure and Stimuli‐Responsive Properties. Issue 5 (17th May 2021) - Shevchenko, Valery; Bliznyuk, Valery; Gumenna, Mariana; Klimenko, Nina; Stryutsky, Alexandr; Wang, Junlei; Binek, Christian; Chernyakova, Margarita; Belikov, Konstantin
Abstract : Back Cover : In article number 2100085 by Valery Shevchenko, Mariana Gumenna, and co‐workers, coordination polymers based on Co 2+, Ni 2+ ions and amphiphilic oligomeric silsesquioxanes, containing various ratios of n‐octadecylurethane and carboxyl groups (OSS‐C18 H37 ‐x‐COOH‐y), form a hierarchical stimuli‐responsive supramolecular structure stabilized by a network of intermolecular hydrogen and coordination bonds. The system possesses superparamagnetic properties due to the formation of metal ion nanoclusters and can be reversibly modified by application of external magnetic field and/or moderate heat.